2018
DOI: 10.23880/eoij-16000130
|View full text |Cite
|
Sign up to set email alerts
|

Helicopter Pilots and Low Back Pain: How to Manage the Risk Factors?

Abstract: A high prevalence of LBP in helicopter pilots has been reported by several epidemiological surveys since the early 1960's. As pointed out by several authors the most important etiologic factor of LBP in helicopter pilots is the asymmetrical posture adopt during flight. The aim of the study is understand the pathomechanical model of the low back pain (LBP) that affects helicopter pilots in order to propose a risk management addressed to reduce this issue. A comprehensive literature review was performed to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 13 publications
(39 reference statements)
4
9
0
Order By: Relevance
“…Studies have suggested a higher prevalence of low back pain in helicopter pilots (HP) when compared to the general population in which the prevalence of spinal pain (SP) in HP ranges from 21 to 95% and the prevalence of low back pain in helicopter pilots during the flight varies from 40 to 100%. This rises a flag to flight safety, since the pain can deconcentrate the pilot, putting human lives in danger and even causing an accident [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies have suggested a higher prevalence of low back pain in helicopter pilots (HP) when compared to the general population in which the prevalence of spinal pain (SP) in HP ranges from 21 to 95% and the prevalence of low back pain in helicopter pilots during the flight varies from 40 to 100%. This rises a flag to flight safety, since the pain can deconcentrate the pilot, putting human lives in danger and even causing an accident [6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most cited primary factor that predisposes helicopter pilots to LBP is the awkward posture adopted by them during the flight [6,10,13,[17][18][19]. To keep the aircraft under control, depending on the layout of the control commands, they should to adopt a posture that is bent forward, with a slight lateral inclination and trunk rotation to the left.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations